The Influence of Organizational Culture and Communication on Accreditation Ranking through Lecturer Performance at Islamic Higher Education Institutions (PIHEIs) in Jambi Province - Murtadlo MS, Ali; Risnita, Risnita; Fadlilah, Fadlilah (Dinasti International Journal of Management Science, 2025)
Accreditation ranking serves as a key quality indicator for higher education institutions, including Private Islamic Higher Education Institutions (PIHEIs). However, organizational factors that drive accreditation success—particularly through the role of lecturer performance—have not been widely examined empirically in the local context. This study employed a quantitative approach using a survey method with 95 respondents from 4 PIHEIs XII in Jambi Province as the sample. Data were analyzed using Structural Equation Modeling with the Partial Least Squares approach (SEM-PLS) to test the direct and indirect effects of Organizational Culture (X1) and Organizational Communication (X2) on Accreditation Ranking (Z) mediated by Lecturer Performance (Y). The results indicate that Organizational Culture has a significant positive effect on Lecturer Performance (?=0.554; p<0.001), but not directly on Accreditation; rather, its effect is fully mediated by Lecturer Performance (?=0.289; p<0.001). Organizational Communication has a significant direct effect on Accreditation (?=0.341; p<0.001), but no significant effect on Lecturer Performance. Lecturer Performance is proven to be the strongest predictor of Accreditation (?=0.521; p<0.001; f²=0.468). The model explains 70.4% of the variance in Accreditation (R²=0.704). The findings suggest that improving PIHEIs accreditation requires a dual strategy: (1) fostering organizational culture to enhance lecturer performance (long-term), and (2) refining communication systems to improve the efficiency of the accreditation process (short-term). Lecturer performance serves as a critical bridge between organizational inputs and institutional outcomes.